El día de la semana con precios bajos: Evidencia sobre la estacionalidad diaria de los precios de alimentos, bebidas y tabaco - Marcelo Delajara; José Antonio Murillo (Banco de México, 2012)
– In this document we analyze the evidence of daily seasonality found in the weekly price variations of food, beverages, and tobacco in the Metropolitan Area of Mexico City. Our research is based on the daily price quotes of 2,724 goods, collected by Banco de México for the Consumer Price Index (CPI), in 434 commercial establishments between March 2009 and June 2010. We identify the weekday with the lowest weekly variation in prices, and find that it differs across products, types of commercial establishment, and supermarket chains. Moreover, we find that such a day of the week effect increases the volatility of the weekly variations of price quotes. These results establish the day of the week among the distinct characteristics of a price, a fact that must be taken into account while preparing calendars for CPI data collection.
Keywords: B4; D4; L16; L81; 330; daily prices; retail sales; seasonal price patterns; dynamic pricing policies; CPI methodologies; Einzelhandel; Einzelhandelspreispolitik; Verbraucherpreisindex; Saisonschwankung; Mexiko-Stadt